2017
DOI: 10.1001/jamadermatol.2017.3182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Comorbidities, Natural History, and Predictors of Early Resolution in a Cohort of Children With Chronic Urticaria

Abstract: IMPORTANCE Chronic urticaria (CU) affects 0.1% to 0.3% of children. Most cases have no identifiable trigger and are classified as chronic spontaneous urticaria (CSU). At least half of patients with CSU may have an autoimmune etiology that can be determined in vitro using the basophil activation test (BAT). While 30% to 55% of CU cases resolve spontaneously within 5 years in adults, the natural history and predictors of resolution in children are not known.OBJECTIVE To assess the comorbidities, natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
71
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 35 publications
12
71
2
3
Order By: Relevance
“…Recently, it was found that positive CD63 basophil activation test is common in PcsU and is associated with high disease activity . Low blood basophil counts on the contrary were linked to earlier symptoms resolution …”
Section: Possible Causes/triggers Of Chronic Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that positive CD63 basophil activation test is common in PcsU and is associated with high disease activity . Low blood basophil counts on the contrary were linked to earlier symptoms resolution …”
Section: Possible Causes/triggers Of Chronic Urticariamentioning
confidence: 99%
“…20 Low blood basophil counts on the contrary were linked to earlier symptoms resolution. 21 Patients suffering from cU can simultaneously have another autoimmune pathology. 22 Thus, antithyroid antibodies can be found in 4.3%-17.3% of children and 27% of adults diagnosed with CSU.…”
Section: P Oss Ib Le C Aus E S/ Tri G G Er S Of Chronic Urtic Ariamentioning
confidence: 99%
“…If urticaria lasts more than 6 weeks, it is defined as chronic urticaria. The prevalence of chronic urticaria in children is about 0.1–0.3% [ 6 ] and it has been found to be more common among atopic patients or patients with familiarity for autoimmune diseases [ 7 ]. In about 80% of cases, chronic urticaria is idiopathic, even if almost half of these patients presents autoantibodies, whose presence could be demonstrated by an autologous skin test [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining patients present inducible forms of urticaria, that can be caused by many different stimuli: physical (such as cold urticaria, dermographic urticaria, delayed pressure urticaria, heat urticaria, solar urticaria, aquagenic urticaria, vibratory angioedema), or by exercise and hot bath (cholinergic urticaria) [ 5 ]. Physical urticarias account for 22% of chronic urticaria in children, and among these dermatographism is the most common [ 7 ]. Recently, European and US guidelines for the diagnosis and the management of CU have been published; the two guidelines are mostly similar even if some differences, especially about treatment, are still present [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous analysis of a larger well-defined CU registry, the natural resolution rate in Canadian children was relatively low, at 10% per year. 4 Further, Canadian and European Academy of Allergy and Clinical Immunology/Global Allergy and Asthma European Network/European Dermatology Forum/World Allergy Organization urticaria guidelines 5,6 recommend that if there is no improvement in the control of symptoms in 2 to 4 weeks of treatment with second-generation antihistamines, the dose should be increased up to 4 times the standard dose, and if inadequate control occurs after 2 to 4 weeks, omalizumab should be added to the treatment. The guidelines do not support waiting 3 months to determine whether resolution occurs.…”
mentioning
confidence: 99%